Draft Five Year Plan 1978-83 Tourism Government of Madhya Pradesh - Planning Commission (Planning Commission, 1978)
To handle the anticipated traffic, 350 additional 'beds' would have to be planned. may assume that 60 % of the additional accommodation would be provided by the ITDC and the private sector hotels. At an average cost of Rs.60,000 per room, the outlay would be Rs.126 lakhs for 210 rooms. Assuming an average of Rs.40,000 per room the outlay would be Rs.56 lakhs.
Government of Madhya Pradesh, Planning, Economics and Statistics Department